PENGEMBANGAN PEMBELAJARAN ILMU PENGETAHUAN SOSIAL SEKOLAH DASAR BERWAWASAN SOSIAL-BUDAYA BERBASIS PAIKEM - Donny Khoirul Azis; Abu Dharin; Hendri Purbo Waseso (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2020)
This paper describes the development of social science (IPS) learning in social-cultural and PAIKEM-based elementary schools. Development of Elementary School Social Sciences Learning based on socio-cultural and PAIKEM-based learning as an innovative step in social studies learning at the elementary school level can minimize deficiencies in teaching students to understand social studies in elementary schools as well as to improve the quality of elementary school social studies learning processes. teachers need to be active, creative and selective in applying learning models and approaches. Based on the main problems and results and discussion as described above, several conclusions can be formulated as follows: 1) learning procedures with learning models with socio-cultural approach provide optimal flexibility for students to improvise during the course of learning so that they can create a climate and conducive learning activities; 2) The effectiveness of the socio-cultural learning model towards increasing understanding of social studies material by students, it appears that students' understanding of the material taught shows an increasing graph, and at the model testing stage, the results of evaluation tests conducted indicate that the average evaluation evaluation score students who are taught by learning models with socio-cultural approaches are higher than the average scores of students who are taught by conventional learning models; and 3) there is an increase in the socio-cultural literacy of students related to the material taught in social studies learning with a socio-cultural approach and based on PAIKEM.